ELEMENTARY SCHOOL STUDENTS’ CREATIVE MATHEMATICAL THINGKING ABILITY THROUGH THE COLLABORATIVE PROBLEM-SOLVING MODEL - Pattimukay, Nessy; Takaria, Johannis; Elwuar, Melati J (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
This research aims to analyze the influence of the Collaborative Problem Solving (CPS) model on mathematical creative thinking abilities (MCTA). The approach used is quasi-experimental with a one-group pretest-posttest design and tested using a paired sample t-test. The research involved 21 fifth-grade students at state elementary school 1 Tual, Maluku Province, Indonesia. The research results show that the CPS model influences MCTA capabilities. By analyzing N-gain, it is found that all KBKM indicators have increased. The fluency indicator increased by 11%, flexibility achieved an increase of 14%, and originality increased by 2%, where all three indicators increased in the low category. This increase is due to the effective use of the CPS learning model. The CPS model triggers students to collaborate in a structured manner, interact, and work together to construct mathematical ideas. In collaborating, students are also encouraged to find various creative ideas for solving mathematical problems.